2014
DOI: 10.3136/fstr.20.687
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Composition, Oxidative Stability, and Consumer Acceptance of Cookies Made with Quinoa Flour

Abstract: Quinoa has strong antioxidant activity and a high amino acid score compared to common cereals such as rice and wheat. Therefore, cookies containing quinoa flour as a substitute for wheat flour were used to investigate the effects of quinoa on the oxidative stability and nutritional quality of the cookies. The antioxidant capacity of the cookies was increased by the addition of quinoa flour. As a result, the peroxide value of cookies containing quinoa was lower than that of cookies without quinoa after storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
3
2
0
Order By: Relevance
“…Several studies reported the impact of quinoa on cookie acceptability, although with contrasting results, whether for wheat‐based or gluten‐free products. As expected, low quinoa enrichment levels (<100 g kg −1 ) did not affect the sensory acceptability of cookies made primarily from wheat flour, but a slightly higher substitution level (150 g kg −1 ) reduced flavour, taste and overall acceptability . However, quinoa cookies were still acceptable, and similar results were observed by Pagamunici et al .…”
Section: Sensory Properties and Acceptability Of Quinoa Food Productssupporting
confidence: 86%
“…Several studies reported the impact of quinoa on cookie acceptability, although with contrasting results, whether for wheat‐based or gluten‐free products. As expected, low quinoa enrichment levels (<100 g kg −1 ) did not affect the sensory acceptability of cookies made primarily from wheat flour, but a slightly higher substitution level (150 g kg −1 ) reduced flavour, taste and overall acceptability . However, quinoa cookies were still acceptable, and similar results were observed by Pagamunici et al .…”
Section: Sensory Properties and Acceptability Of Quinoa Food Productssupporting
confidence: 86%
“…Unfortunately, despite the health benefits attributed to quinoa and recognised world-wide, the presence of bitter compounds in the quinoa flour, which include saponins and phenolic compounds, can affect the sensory characteristics of quinoa-based products [39]. The negative effects reported in this study confirm the data found in the literature [54,55], indicating that increasing the QF level in Summary results of the penalty analysis put in evidence that herbaceous and dry in mouth are characteristics that the ideal biscuit must not have, whereas the main drivers of preference are the following attributes (Table 5): nice colour, sweet, good for breakfast, good for taste, nice appearance, soft in mouth, and good odour. Unfortunately, despite the health benefits attributed to quinoa and recognised world-wide, the presence of bitter compounds in the quinoa flour, which include saponins and phenolic compounds, can affect the sensory characteristics of quinoa-based products [39].…”
Section: Sensory Analysissupporting
confidence: 74%
“…Unfortunately, despite the health benefits attributed to quinoa and recognised world-wide, the presence of bitter compounds in the quinoa flour, which include saponins and phenolic compounds, can affect the sensory characteristics of quinoa-based products [39]. The negative effects reported in this study confirm the data found in the literature [54,55], indicating that increasing the QF level in the biscuit formulation results in a decrease in colour, taste, odour, flavour, general appearance, and overall acceptability ratings of Q-based biscuits. New approaches aimed at decreasing the bitterness of quinoa flour need to be explored.…”
Section: Sensory Analysissupporting
confidence: 74%
“…In our study, the baking temperature and time were 160 °C and 13 min, respectively, which were lower than those in previous studies. A similar study was carried out by Watanabe et al (2014), who evaluated the storage stability of fat contained in cookies made with 7.5% and 15% quinoa flour instead of wheat flour. Their results showed that the antioxidants present in quinoa cookies could inhibit the oxidation of the fats contained in them.…”
Section: Consumer Testmentioning
confidence: 93%